Hsa-miR-196a2 functional SNP is associated with the risk of ESCC in individuals under 60 years old. (February 2014) - Wang, Na; Li, Yan; Zhou, Rong-Miao; Wang, Gui-Ying; Wang, Chun-Mei; Chen, Zhi-Feng; Liu, Wei
Abstract Background and aim: The miR-196a2 gene contains a C/T polymorphism (rs11614913). Its presence could change the conformation of secondary structure of miR-196a2 RNA, and directly affect the binding to target mRNAs and the miRNA maturation process. Both of which eventually alter protein expression and contributed to cancer susceptibility. This study assessed whether the rs11614913 single nucleotide polymorphism (SNP) could affect an individual's susceptibility to esophageal squamous cell carcinomas (ESCC). Methods: SNP rs11614913 was genotyped by polymerase chain reaction ligase detection reaction (PCR-LDR) in 597 ESCC patients and 597 control subjects. Results: Overall, there were no significant differences in the frequency of the miRNA-196a2 SNP rs11614913 genotype between the ESCC cases and the controls (χ2 = 1.395, p = 0.498). The TT genotype, CT genotype and CT/TT combined genotype (dominant model) did not modify the risk of ESCC as compared with the CC genotype. Comparisons of the TT genotype to the CT/CC combined genotype did not reveal a significant association to ESCC, too. However, further analyses revealed an increased risk of ESCC in the dominant model (OR = 1.56, 95% CI = 1.08–2.26) and the allele frequency comparison (OR = 1.31, 95% CI = 1.06–1.63) in the ≤60-year-old group. Conclusions: These results suggest that the miRNA-196a2 functional polymorphism rs11614913 might be an effective genetic marker for ESCC risk assessment in individuals younger than 60 years of age from a region of high ESCC incidence in northern China.